2020
DOI: 10.1002/jsfa.10857
|View full text |Cite
|
Sign up to set email alerts
|

Does a coffee plantation host potential pollinators when it is not flowering? Bee distribution in an agricultural landscape with high biological diversity in the BrazilianCampo Rupestre

Abstract: BACKGROUND Natural environments within agricultural landscapes have been recognized as reservoirs of biodiversity and, therefore, providers of fundamental ecosystem services to human beings. Bees are the main providers of pollination and thus contribute to the production of food consumed worldwide. In this work, we evaluated the distribution of bees in an agricultural landscape of coffee plantation before and after coffee flowering. We aimed at understanding how richness, abundance and composition of bee commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…One way to deliver this productive increase for the entire plantation would be to provide resources and nesting opportunities inside or close the coffee plantation to increase bee nesting sites and abundance throughout the coffee planted area. Machado et al (2020) showed that the studied region has a high diversity of bees and in this study, bees built many nests in the border area and native vegetation. However, bees built fewer nests inside the coffee plantation, probably because there are no constant nest and floral resources that provide conditions for them to become resident.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…One way to deliver this productive increase for the entire plantation would be to provide resources and nesting opportunities inside or close the coffee plantation to increase bee nesting sites and abundance throughout the coffee planted area. Machado et al (2020) showed that the studied region has a high diversity of bees and in this study, bees built many nests in the border area and native vegetation. However, bees built fewer nests inside the coffee plantation, probably because there are no constant nest and floral resources that provide conditions for them to become resident.…”
Section: Discussionsupporting
confidence: 50%
“…It is clear from our results that coffee crop areas and native surrounding vegetation represent complementary dimensions of coffee pollinator niches, that is foraging and nesting. Moreover, the surroundings are the main source of pollinator food when coffee is not flowering (Machado et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting high densities of managed honeybees, alongside wild pollinator populations, requires the maintenance of temporally consistent high floral densities. Therefore, management that maintains high densities of flowering forbs in the landscape is essential to maintaining farm multifunctionality (Machado et al, 2021).…”
Section: Management Implicationsmentioning
confidence: 99%
“…One of the most important ecosystem services is biotic pollination; 10 this service provides the world with an estimated annual profit ranging from nearly US $235 to 577 11 Over 70% of crop species depends to some extent on biotic pollination 12 . Biotic pollination is undermined by the degradation and fragmentation of the natural habitat in the region surrounding the agricultural matrix, since the lack of natural resources in this region negatively affects the diversity of pollinators 13‐17 …”
Section: Introductionmentioning
confidence: 99%
“…12 Biotic pollination is undermined by the degradation and fragmentation of the natural habitat in the region surrounding the agricultural matrix, since the lack of natural resources in this region negatively affects the diversity of pollinators. [13][14][15][16][17] Several studies reported in the literature have shown that biotic pollination increases coffee productivity. [18][19][20][21][22][23][24][25][26][27] Although coffee is a self-compatible crop, the production of Arabica coffee is increased significantly when biotic pollinators take part in the cultivation process.…”
Section: Introductionmentioning
confidence: 99%